2005
DOI: 10.3928/1081-597x-20050901-09
|View full text |Cite
|
Sign up to set email alerts
|

Moria M2 Single Use Microkeratome Head in 100 Consecutive LASIK Procedures

Abstract: PURPOSE: To evaluate the safety and efficacy of the Moria M2 single use 130 microkeratome head in consecutive LASIK procedures for correction of myopia and myopic astigmatism. METHODS: One hundred eyes of 55 patients underwent LASIK in which the flaps were created with the Moria M 2 microkeratome using the single use 130 head and excimer laser ablation was done with the Allegretto Wavelight laser. Flap parameters measured were: thickness, diameter, hinge length, and overall quality. Preoperative unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…In our study, the M2 single use head tended to cut less (106Ϯ17 µm) than the manufacturer expected (120 µm), although with a large range (65 to 152µm). The M2 90-µm single use head seems to cut thinner fl aps with smaller variability, comparable not only to other Moria heads 14,15,[17][18][19][20][21] but also to other microkeratomes with different heads. 17,19,20,[22][23][24][25][26] The mean fl ap thickness in the second (left) eye was approximately 5.5% thinner than in the fi st (right) eye (103Ϯ15 µm compared to 109Ϯ18 µm), which is in agreement with other studies.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In our study, the M2 single use head tended to cut less (106Ϯ17 µm) than the manufacturer expected (120 µm), although with a large range (65 to 152µm). The M2 90-µm single use head seems to cut thinner fl aps with smaller variability, comparable not only to other Moria heads 14,15,[17][18][19][20][21] but also to other microkeratomes with different heads. 17,19,20,[22][23][24][25][26] The mean fl ap thickness in the second (left) eye was approximately 5.5% thinner than in the fi st (right) eye (103Ϯ15 µm compared to 109Ϯ18 µm), which is in agreement with other studies.…”
Section: Resultssupporting
confidence: 60%
“…The mean fl ap diameter was 9.4Ϯ0.3 mm (range: 8.5 to 9.9 mm) and the mean hinge chord size was 4.4Ϯ0.4 mm (range: 3.8 to 6 mm) ( Figs 3 and 4). 14 The concept of a disposable microkeratome has been investigated and introduced in clinical practice by a number of manufacturers, but it was not until the fi rst encouraging results with the Moria M2 single use 130 head 15 had it been shown that with an adequate design or plastic material choice, the increased fl ap-related complications with other disposable microkeratomes 16 can be overcome.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular MKs for LASIK are based on the oscillating blade principle. The Moria M2 (Antony, France) is a popular compact automated MK with mechanical stop designed for maximum safety [ 10 ]. Currently, five femtosecond (FS) lasers are licensed for LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…При измерении диаметра роговичного клапана, сформированного с помощью фемтосекундного лазера, стандартное отклонение составляет не более 0,2 мм [18]. Аналогичный морфометрический параметр клапана, полученный по результатам работы микрокератома, может достигать 0,4 мм, что говорит о большей девиации значений диаметра клапана при использовании микрокерато-ма [19]. Это приводит к повышенному риску повреждения новообразованных сосудов на периферии роговицы с последующим кровотечением и увеличением времени операции, а также к воздействию эксимерного лазера за пределами стромального ложа роговицы и возможному врастанию эпителия под клапан.…”
Section: Introductionunclassified